The Optimization of UV/H 2 O Process for DYA (Dianic Yellow Ace) Textile-Dye Wastewater Treatment - Tedi Hudaya; Geoffery Hariyanto; Winda Andriany (Seminar Nasional Teknik Kimia Kejuangan, 2017)
West Java region, especially in Bandung area, has many textile dyeing industries which are usually placed in a densely populated area. If not properly handled, the wastewater effluents will cause considerable pollution problems to the surrounding water streams due to toxic and non-biodegradable synthetic dyes content characterized by a very low BOD5/COD ratio (< 0.1). This research studied the application of UV/H2O2 method for treating textile-dye (Dianic Yellow Ace – DYA) waste water in a pilot scale (50 L) multi-lamp bubble column photoreactor. The prime target of the treatment was to increase the BOD5/COD ratio until the biodegradability threshold was reached (> 0.1), prior to further treatment by a cheaper conventional biological method. Two major operating conditions, the initial H2O2 concentration and pH were varied, using Central Composite Design, between 0.026 – 0.874 % w/w, and 0.17 – 5.83, respectively. This study used a synthetic wastewater with color content similar to a real waste water from a textile dyeing industry in Bandung. Within the experimental condition range, 51 – 94% color content was successfully eliminated within 6 hours illumination period using 3 x 75 Watt low pressure Hg UV lamp. Optimum conditions from 2nd order model optimization showed that the best result of 95.5% color removal could be obtained at initial H2O2 concentration of 0.53 % w/w and pH 3.35. Additional test with a real industrial wastewater under 5 x 75 Watt UV irradiation under those best conditions resulted in BOD5/COD ratio increase from 0.01 to 0.1(biodegradability threshold) within 9.5 hours.